2012
DOI: 10.1007/jhep05(2012)092
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop corrections to the B → π form factor from QCD sum rules on the light-cone and |Vub|

Abstract: We calculate the leading-twist O(α 2 s β 0 ) corrections to the B → π transition form factor f + (0) in light-cone sum rules. We find that, as expected, there is a cancellation between the O(α 2 s β 0 ) corrections to f B f + (0) and the large corresponding corrections to f B , calculated in QCD sum rules. This suggests the insensitivity of the form factors calculated in the light-cone sum rules approach to this source of radiative corrections. We further obtain an improved determination of the CKM matrix elem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 71 publications
(114 reference statements)
3
58
1
Order By: Relevance
“…For B → π FFs it has been found that a conversion to the MS-scheme leads to minor changes only [20,53]. The explicit appearance of m b in the EOM (2.6)-(2.9) deserves a reinvestigation of the issue of scheme dependence.…”
Section: A5 Scheme Dependence Of the Form Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For B → π FFs it has been found that a conversion to the MS-scheme leads to minor changes only [20,53]. The explicit appearance of m b in the EOM (2.6)-(2.9) deserves a reinvestigation of the issue of scheme dependence.…”
Section: A5 Scheme Dependence Of the Form Factorsmentioning
confidence: 99%
“…SR only increases by 2% [53]. Therefore we make use of the QCD sum rules result at O(α s ) [54,55] for f B .…”
Section: Input Parameters and Uncertaintiesmentioning
confidence: 99%
“…We use the expressions for OPE derived in [7] extending them to the B → K and B s → K cases (see also [18]). We do not include the O(β 0 ) estimate of the twist-2 O(α 2 s ) contribution to the twist-2 hard-scattering amplitude calculated in [44], since the resulting effect in LSCR is very small and does not yet represent a complete NNLO computation of T (2) 1 . The analytic result for 2 ) is matched to the hadronic dispersion relation for the correlation function (A.1) in the variable (p + q) 2 .…”
Section: Jhep08(2017)112mentioning
confidence: 99%
“…For our analysis, we take the results from light cone QCD sum rules (LCSR), which are typically calculated at q 2 = 0. The relevant form factors are f + B→π (0) = 0.252 +0.019 −0.028 [36], f + B→K (0) = 0.34 +0.05 −0.02 [37] and f + Bs→K (0) = 0.30 +0.04 −0.03 [38], where the first two describe transitions for both the B 0 d and the B + mesons. The q 2 dependence of these form factors is parametrised by means of the BGL method described in ref.…”
Section: Jhep03(2015)145mentioning
confidence: 99%